2018
DOI: 10.7717/peerj.5669
|View full text |Cite
|
Sign up to set email alerts
|

From the cage to the wild: introductions of Psittaciformes to Puerto Rico

Abstract: Introduced psittacine birds can become highly invasive. In this study, we assessed invasions of Psittaciformes in Puerto Rico. We reviewed the literature, public databases, citizen science records, and performed in situ population surveys across the island to determine the historical and current status and distribution of psittacine species. We used count data from Ebird to determine population trends. For species whose populations were increasing, we modelled their potential distribution using niche modeling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 94 publications
2
32
0
Order By: Relevance
“…In contrast, however, they found that White-winged Parakeets and Monk Parakeets have greatly expanded their range on Puerto Rico in recent years, which is consistent with atlas results indicating that both species are widespread. Although Falcón and Tremblay (2018) found that populations of Red-masked Parakeet and Orange-fronted Parakeet showed only slight range expansions on the island, the atlas results indicate that both species remain localized near their presumed release sites. Similarly, the introduced Java Sparrow described as limited to the San Juan metropolitan area, especially Old San Juan (Oberle 2018, Raffaele 1989a, remains restricted to that area as also documented in the atlas.…”
Section: Atlas Results and Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In contrast, however, they found that White-winged Parakeets and Monk Parakeets have greatly expanded their range on Puerto Rico in recent years, which is consistent with atlas results indicating that both species are widespread. Although Falcón and Tremblay (2018) found that populations of Red-masked Parakeet and Orange-fronted Parakeet showed only slight range expansions on the island, the atlas results indicate that both species remain localized near their presumed release sites. Similarly, the introduced Java Sparrow described as limited to the San Juan metropolitan area, especially Old San Juan (Oberle 2018, Raffaele 1989a, remains restricted to that area as also documented in the atlas.…”
Section: Atlas Results and Discussionmentioning
confidence: 62%
“…Like the introduced finches in novel habitats, introduced parrots, parakeets, cockatoos, and macaws (psittacines) have also become naturalized in novel urban, suburban, and forest habitats on Puerto Rico (Raffaele 1989a(Raffaele , 1989b. More recently, Falcón and Tremblay (2018) report that 29 nonnative psittacine species have been observed in the wild on Puerto Rico, of which 12 species have been found breeding, but most with small populations, which are highly localized. In contrast, however, they found that White-winged Parakeets and Monk Parakeets have greatly expanded their range on Puerto Rico in recent years, which is consistent with atlas results indicating that both species are widespread.…”
Section: Atlas Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species are widely distributed around the globe as pets. However, feral individuals of both of these species have been observed in Puerto Rico, although they are rare sightings, and no breeding populations have been detected [ 46 ]. Despite the dominance of chickens and the abundance of native bird species, we were still able to detect these rare feeding events on pet birds.…”
Section: Discussionmentioning
confidence: 99%
“…In Puerto Rico, barrages of new, invasive species are being introduced (e.g., Rojas-Sandoval & Acevedo-Rodríguez, 2016;Falcón & Tremblay, 2018). Often overlooked are the increasing numbers of exotic orchids (Ackerman, 2007).…”
Section: Introductionmentioning
confidence: 99%